2017
DOI: 10.1116/1.5013335
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing cell and gene therapy manufacture through the application of advanced fluorescent optical sensors (Review)

Abstract: Cell and gene therapies (CGTs) are examples of future therapeutics that can be used to cure or alleviate the symptoms of disease, by repairing damaged tissue or reprogramming defective genetic information. However, despite the recent advancements in clinical trial outcomes, the path to wide-scale adoption of CGTs remains challenging, such that the emergence of a “blockbuster” therapy has so far proved elusive. Manufacturing solutions for these therapies require the application of scalable and replicable cell m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…In situ monitoring of cellular health in bioreactors is a challenge for industrial bioprocessing to ensure batch-to-batch reproducibility, maximize the yield of production, and reduce the risk of contamination associated with sampling procedures [46][47][48]. In addition to the measurement of metabolites in the culture medium such as O 2 , CO 2 , or pH, production of fluorescent proteins (FPs) such as green fluorescent protein (GFP) have been recently introduced as a reporter of the status of cells or bacteria in bioreactors, which in turn allows feedback control for the culture conditions when needed [47,49] using, e.g., optogenetic tools [50,51].…”
Section: Sensitive Tool To Monitor Gene Expression In Bioreactorsmentioning
confidence: 99%
“…In situ monitoring of cellular health in bioreactors is a challenge for industrial bioprocessing to ensure batch-to-batch reproducibility, maximize the yield of production, and reduce the risk of contamination associated with sampling procedures [46][47][48]. In addition to the measurement of metabolites in the culture medium such as O 2 , CO 2 , or pH, production of fluorescent proteins (FPs) such as green fluorescent protein (GFP) have been recently introduced as a reporter of the status of cells or bacteria in bioreactors, which in turn allows feedback control for the culture conditions when needed [47,49] using, e.g., optogenetic tools [50,51].…”
Section: Sensitive Tool To Monitor Gene Expression In Bioreactorsmentioning
confidence: 99%
“…Since the production of fluorescent nanosensors, a number of ratiometric fluorescence nanosensors for pH (Chauhan et al 2013; Orsi et al 2015; Elsutohy et al 2017) have been reported based on polymeric nanoparticles, silica nanoparticles, quantum dots, cellulose nanocrystals, latex nanobeads, and zeolite-based nanoparticles (Marín et al 2012). Overall, fluorescent nanosensors are useful for sensing due to their small size, fast response, intense signal, against relatively low background noise, relatively simple instrumental set-up, and ability to monitor non-invasively (Harrison and Chauhan 2018).…”
Section: Fluorescence Probes For Monitoringmentioning
confidence: 99%
“…Small-scale culture of cells is typically used for in vitro research studies based on micro and milli scale volumes. Large scale culture for clinical use have been developed with volumes of up to 20,000 litres (Harrison and Chauhan 2018 ). Some examples of large scale production for clinical applications include adipose-derived stromal cells for tissue engineering (Haack-Sørensen et al 2018 ), human induced pluripotent stem cells for drug screening regenerative medicine (Yamashita et al 2018 ), megakaryocytic progenitor cell line for regenerative medicine (Retno Wahyu et al 2018 ) and mesenchymal stem cell for cartilage tissue generation (Daly et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Small-scale bioreactors are used for in vitro research purposes or clinical allogeneic products in commercial settings, such as chimeric antigen receptor (CAR) T cells [77]. Whereas, large-scale manufacture, which can reach batch sizes of 20,000 liters, are typically used for commercial projects [78].…”
Section: Bioreactors and Fluorescent Nanosensorsmentioning
confidence: 99%